O Ministério Público do Estado de São Paulo e o seu plano geral de atuação - Sampaio, Marianna (2017)
This thesis has as empirical object the General Plan of Action of the Public Prosecutor's Office of the State of São Paulo, instrument through which the annual priority goals are set and which prosecutors are required to take into account in the performance of their duties. The background and track record of the General Plan, as well as the classification of the type of goal that it is comprised of, are examined in order to carry out an analysis on the internal organization of the Public Prosecutor's Office and the possible contribution of prosecutors to the phenomenon of judicialization of politics. It also seeks to understand how the relationship is set between the formalization of an institutional policy such as the General Plan of Action and the constitutional principle of the functional independence of the Public Prosecutor's Office.